Sustainable Tourism and Local Culture Preservation: Insights from Penglipuran Village Bali - I Ketut Surata; I Putu Sarjana (International Journal of Multidisciplinary Sciences, 2026)
This study examines the impact of cultural tourism on the preservation of local traditions in Penglipuran Village, one of Bali’s recognized tourism villages. While previous research has extensively discussed the economic and environmental consequences of tourism, limited attention has been given to its influence on the sustainability of local cultural traditions at the village level. Moreover, existing studies tend to adopt general perspectives, lacking in-depth analysis of specific socio-cultural dynamics within particular communities. This research employs a qualitative approach using a case study design to explore how cultural tourism interacts with traditional practices in Penglipuran Village. Data were collected through field observation, interviews with community leaders and residents, and document analysis. The findings indicate that although tourism has introduced certain transformations in ritual practices and social organization, the community’s strong adherence to fundamental Hindu philosophical doctrines, such as Widhi Tattwa, Atman Tattwa, Karmaphala Tattwa, Samsara Tattwa, and Moksa Tattwa, serves as a stabilizing framework that sustains cultural continuity. Local perceptions suggest that tourism, rather than eroding tradition, can reinforce cultural preservation due to visitors’ interest in authenticity and ritual life. Strategic measures implemented include participatory tourism governance, cultural education programs, infrastructure development, sustainable mobility systems, community-based partnerships, small enterprise empowerment, experiential and educational tourism packages, regulatory frameworks, systematic documentation, and community capacity building. This study contributes to the discourse on sustainable cultural tourism by demonstrating how religious worldview and community-based management function as key mechanisms in safeguarding local traditions.